2019
DOI: 10.1177/0143034319854474
|View full text |Cite
|
Sign up to set email alerts
|

Perceived school kindness and academic engagement: The mediational roles of achievement goal orientations

Abstract: Perceptions of kindness at school have been linked to a few positive psychological outcomes including optimism, happiness, life satisfaction, and social goals. However, limited evidence has been generated on how kindness relates to academic-related outcomes. This study explored the association of perceived school kindness with different domains of academic engagement. It also examined whether school kindness would have indirect effects on engagement outcomes via the intermediate variables – achievement goal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 51 publications
0
22
1
5
Order By: Relevance
“…Existing literature has offered inconsistent evidence on how specific interpersonal character strengths relate to academic-related functioning like academic achievement (Park & Peterson, 2006) and engagement (Datu & Park, 2019; Hausler et al, 2017). For example, teamwork and leadership are related to higher achievement among German primary school students, but not among secondary school students (Wagner & Ruch, 2015).…”
Section: Interpersonal Strengths and Academic Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing literature has offered inconsistent evidence on how specific interpersonal character strengths relate to academic-related functioning like academic achievement (Park & Peterson, 2006) and engagement (Datu & Park, 2019; Hausler et al, 2017). For example, teamwork and leadership are related to higher achievement among German primary school students, but not among secondary school students (Wagner & Ruch, 2015).…”
Section: Interpersonal Strengths and Academic Outcomesmentioning
confidence: 99%
“…In a sample of law students in the United States, the interpersonal character strengths as a factor negatively predicted grade point average in male students (Kern & Bowling, 2015). Yet kindness is linked to greater academic engagement among selected Filipino high school students (Datu & Park, 2019). The inconsistent and even contrary findings among these students’ samples from WEIRD societies may reflect the possibility that interpersonal strengths are not typically associated with achievement-related motivations in these societies.…”
Section: Interpersonal Strengths and Academic Outcomesmentioning
confidence: 99%
“…A range of contributory factors, including school climate as a whole rather than pedagogy alone, should therefore be accounted for in research. This is supported by existing evidence demonstrating school environments that foster kindness or adopt a whole-school socio-emotional ethos are associated with higher academic engagement and achievement (Banerjee et al, 2014;Datu and Park, 2019). Futhermore, a recent review of school-based wellbeing programs found they had a small to moderate positive impact on pupils' academic achievemen in both literacy and Maths, compared to pupils in control groups engaged in their typical activities with general academic performance (Dix et al, 2020).…”
Section: Existing Evidence and Unexplored Landmentioning
confidence: 86%
“…Among the antecedents of student engagement, past studies have focused on the critical role played by personal factors. A wide range of psychological antecedents such as motivational internalization (Froiland & Worrell, 2016), interest (Patall, Vasquez, Steingut, Trimble, & Pituch, 2016), self-efficacy beliefs (Chong, Liem, Huan, Kit, & Ang, 2018), achievement goals (Datu & Park, 2019; Duchesne, Larose, & Feng, 2019), implicit theories of ability (Dupeyrat & Mariné, 2005), and personality traits (Komarraju & Karau, 2005) among others have been identified as key predictors of student engagement.…”
Section: Student Engagement In Schoolmentioning
confidence: 99%